Community-based prevalence of rheumatic heart disease in rural Ethiopia: Five-year follow-up - Gemechu, Tadesse; Parry, Eldryd H. O.; Yacoub, Magdi H.; Phillips, David I. W.; Kotit, Susy (PLOS Neglected Tropical Diseases, 2021)
Author summary Although chronic rheumatic heart disease is one of the most important causes of heart disease in sub-Saharan Africa it is still poorly understood. In particular, little is known about the frequency, severity and progression of the disease in the rural areas where most of the population live. In 2017, we reported the results of a community-based study in a rural area of south-west Ethiopia using ultrasound imaging of the heart (echocardiography) which showed a high prevalence of the disease. In a follow-up of the cases originally identified in the study, we found that there was considerable variability of the disease with some individuals showing progression and others regression of the heart abnormalities. The majority of affected individuals, however, had evidence of continuing disease five years later. We also found an increased risk in the family relatives of cases, notably among siblings. Although affected individuals were instructed to take prophylactic penicillin to prevent the disease progressing, compliance with this was very poor. The findings highlight the problems faced in addressing rheumatic heart disease in rural Africa. They suggest that community-based interventions will be required together with innovative ways of identifying active cases, achieving adequate antibiotic prophylaxis and primary prevention.